2015
DOI: 10.1128/aem.04020-14
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Study of Vibrio parahaemolyticus Prevalence and Distribution in New Zealand Shellfish

Abstract: bThe food-borne pathogen Vibrio parahaemolyticus has been reported as being present in New Zealand (NZ) seawaters, but there have been no reported outbreaks of food-borne infection from commercially grown NZ seafood. Our study determined the current incidence of V. parahaemolyticus in NZ oysters and Greenshell mussels and the prevalence of V. parahaemolyticus tdh and trh strains. Pacific (235) and dredge (21) oyster samples and mussel samples (55) were obtained from commercial shellfish-growing areas between D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 29 publications
6
37
1
Order By: Relevance
“…) published by Cruz et al . (). Vibrio vulnificus was detected in 13·6% of Pacific oyster samples ( n = 32) harvested from the North Island, and was not detected in any samples from the South Island ( n = 18).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…) published by Cruz et al . (). Vibrio vulnificus was detected in 13·6% of Pacific oyster samples ( n = 32) harvested from the North Island, and was not detected in any samples from the South Island ( n = 18).…”
Section: Resultsmentioning
confidence: 97%
“…), although it was not as clear as that in the parallel V. parahaemolyticus study (Cruz et al . ). The frequency of positive samples for V. vulnificus was significantly higher in summer months than in winter months (June–November vs December–May, P < 0·01).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…While vibrios are often particle attached, Lopez-Hernandez et al [42] hypothesized that non-digestible particles led to downshifts in filter-feeding in oysters. In Brazil, V. parahaemolyticus was found to be negatively correlated with salinity, and studies in New Zealand have demonstrated that salinity is unrelated or negatively correlated to V. parahaemolyticus shellfish abundances, depending on the study [43,44].…”
Section: Introductionmentioning
confidence: 99%